2019
DOI: 10.3390/app9091783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vehicular Speed on the Assessment of Pavement Road Roughness

Abstract: Good ride quality is a fundamental requirement for all road networks in modern countries. For this purpose, it is essential to monitor and evaluate the effect of irregularities on road pavement surfaces. In the last few decades, many roughness indices have been proposed, with the aim to represent shortly the pavement surface characteristics and the relative performances, using a single number and a correspondent scale of values. In this work, a comparison between three different evaluation methods (Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Three acceleration values were considered: 0.315 m/s 2 , an upper band of the “not uncomfortable” reaction level (Table 1); 0.63 m/s 2 , an upper band of the “a little uncomfortable” reaction level; and 0.9 m/s 2 , an average of the upper band of the “fairly uncomfortable” level (1 m/s 2 ) and the lower band of the “uncomfortable” level (0.8 m/s 2 ). These acceleration limit values were in line with other proposals ( 17, 18, 30, 56 ).…”
Section: Iri Thresholds Based On Wbv Measurementsupporting
confidence: 92%
See 2 more Smart Citations
“…Three acceleration values were considered: 0.315 m/s 2 , an upper band of the “not uncomfortable” reaction level (Table 1); 0.63 m/s 2 , an upper band of the “a little uncomfortable” reaction level; and 0.9 m/s 2 , an average of the upper band of the “fairly uncomfortable” level (1 m/s 2 ) and the lower band of the “uncomfortable” level (0.8 m/s 2 ). These acceleration limit values were in line with other proposals ( 17, 18, 30, 56 ).…”
Section: Iri Thresholds Based On Wbv Measurementsupporting
confidence: 92%
“…They used 120 sections of length, L = 320 m. IRI thresholds were derived for a wSz = 0.315, 0.63, and 0.90 m/s 2 as IRI = a wSz / b 1 . Similar parameters of dependence a wSz = f (IRI) and IRI thresholds were calculated by Loprencipe et al ( 30 ) for 621 real road sections of a total length of 200 km.…”
Section: Iri Thresholds Based On Wbv Measurementsupporting
confidence: 56%
See 1 more Smart Citation
“…where W k,I are the frequency weightings in one-third octave bands for seated position, provided by the standards, and a iz is the vertical RMS acceleration for the i-th one-third octave band. This method ( Figure 3) allowed the evaluation of the vertical accelerations in order to analyze the comfort of car passengers [39,45,46].…”
Section: Methodsmentioning
confidence: 99%
“…Loprencipe et al evaluated the use of IRI index for the road unevenness in relation to the road users' comfort, confirming the results obtained by Ahlin et al that indicated that sometimes IRI can lead to incorrect and not accurate results because in its calculation the contribution provided by some frequencies is underestimated or even not considered. Thus, it can happen that two pavements profiles having the same IRI value can induced completely different acceleration levels [13].…”
Section: Introductionmentioning
confidence: 99%